Analysis of Regional Regulation of Sleman Regency Number 15 Year 2020 Based on Local Wisdom - Antonius Satriyo Adi Pradana; Syukron Abdul Kadir; Benedictus Hestu Cipto Handoyo (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2023)
Sleman Regency Regional Regulation Number 15 of 2020 refers to concurrent government affairs that are not related to Basic Services, namely investment with the aim of encouraging investment and business activities, supporting economic growth, and contributing the public and private sectors to regional development through providing incentives and/or investment promotion. The purpose of this research is to find out whether there is politicization from the formation of this regulation, find out the form of local wisdom contained, and how far the usefulness of this regulation has been. The research conducted is normative legal research with descriptive research. The research concluded that this regulation aims to support the SLEMAN SEMBADA slogan, especially in terms of prosperity and equity. The benefits obtained are that it has succeeded in maintaining Sleman as the regency with the highest income in DIY Province.